Wakaf Unit Amanah: Sorotan Fatwa Semasa - Syahnaz Sulaiman; Aznan Hasan; Azman Mohd Noor (Usuli Faqih Research Centre PLT, 2024)
Waqf institutions have contributed significantly towards the advancement of ummah during the golden era of Islamic civilization. In line with rapid development of Islamic financial system throughout the world, unit trust has been identified as one of the financial instruments to have potential as waqf asset. Such approach is also supported by an efficient and professional manner in managing waqf assets. However, the concept of unit trust waqf is stil at an infancy stage that requires further in-depth study on its mechanism and implementation. This study conducts a review of literature with respect to the current fatawa (Islamic legal rulings) pertaining to unit trust waqf. The main objective of this study was achieved through content analysis of the classical and contemporary books as well as fatawa associated to financial instruments including unit trusts. The finding is expected to pave the way in generating some insight to waqf managers, regulators and fund managers in establishing a dynamic and viable unit trust waqf to be implemented in Malaysia.